Pengaruh Implementasi Budaya Patient Safety Terhadap Efektifitas Pencegahan Adverse Event - Subekti, Siti Rohmah; Hadi, Muhammad; Naryati, Naryati; Kurniati, Tri; Sumartini, Tini (Universitas Malahayati, 2024)
ABSTRACT Patient safety is a framework of organized activities to reduce the occurrence of avoidable harms and mitigate their impact when they occur. Many factors influence the prevention of adverse events in hospital patients. Hospitals must implement a service based on patient safety by every health worker to maintain and improve the quality of nursing care. This research aims to determine effectivenessimplementation of patient safety culture on the effectiveness of preventing unwanted events (adverse events).The method used in this research is Generalized Linear Model Repeated Measure (GLM-RM) which is used to analyze the effectiveness ofimplementation of patient safety culture on the effectiveness of preventing adverse events in inpatient settingsin the control and intervention groups. From the results of the generalized linear model repeated measure (GLM-RM), a comparison of the prevention of adverse events in the intervention group and the control group after the implementation of patient safety culture was obtained with a mean difference =66.8 with a p-value = 0.000. The results of the General Linear Model Repeated Measure showed that Mauchly's test of sphericity showed a significance value of 0,00, and the test of between-subjects effects showed that there was a difference in the prevention of adverse events with a p-value = 0.000 between the two groups. Based on the estimated parameter test, there is a difference in the prevention of adverse events from time to time with a p- value = 0.000.The conclusion from this research is that there is effectivenessimplementation of patient safety culture on the effectiveness of preventing adverse events in inpatient care. Keywords: Adverse Event, Patient Safety Culture ABSTRAK Keselamatan pasien adalah kerangka kerja kegiatan terorganisir untuk mengurangi terjadinya bahaya yang dapat dihindari dan mengurangi dampaknya ketika hal itu terjadi. Banyak faktor yang mempengaruhi pencegahan kejadian tidak diharapkan (adverse event) pada pasien di rumah sakit. Rumah sakit harus menerapkan suatu pelayanan berbasiskan keselamatan pasien oleh setiap tenaga kesehatan untuk menjaga dan meningkatkan kualitas asuhan keperawatan. Penelitian ini bertujuan untuk mengetahui efektifitas implementasi budaya patient safety terhadap efektifitas pencegahan kejadian tidak diinginkan (adverse event). Metode yang digunakan dalam penelitian ini adalah Generalized Linear Model Repeated Measure (GLM-RM) yang dimana untuk menganalisia efektifitas implementasi budaya patient safety terhadap efektifitas pencegahan kejadian tidak diinginkan (adverse event) di Rawat Inap pada kelompok kontrol dan intervensi. Dari hasil generalized linear model repeated measure (GLM-RM) didapatkan perbandingan pencegahan kejadian tidak diharapkan (adverse event) pada kelompok intervensi dan kelompok kontrol sesudah penerapan budaya patient safety dengan nilai mean difference=66,8 dengan p-value=0,000. Hasil General Linier Model Repeated Measure didapatkan nilai mauchly’s test of sphericity didapatkan nilai signifikansi 0,000, dan uji test of between –subjects effects didapatkan hasil bahwa terdapat perbedaan pencegahan kejadian tidak diharapkan (adverse event) dengan nilai p-value=0,000 antara kedua kelompok. Berdasarkan uji parameter estimates, terdapat perbedaan pencegahan kejadian tidak diharapkan (adverse event) dari waktu ke waktu dengan nilai p-value =0,000. Kesimpulannya dari penelitian ini adalah terdapat efektifitas implementasi budaya patient safety terhadap efektifitas pencegahan kejadian tidak diinginkan (adverse event) di Rawat Inap. Kata Kunci: Adverse Event, Budaya Patient Safety